Synchrotron-based infrared microspectroscopy study on the radiosensitization effects of Gd nanoparticles at megavoltage radiation energies. Issue 18 (8th August 2019) - Martínez-Rovira, Immaculada; Seksek, Olivier; Puxeu, Josep; Gómez, Joan; Kreuzer, Martin; Dučić, Tanja; Ferreres, Maria Josep; Artigues, Manel; Yousef, Ibraheem
Abstract : Synchrotron-based infrared microspectroscopy is a powerful technique for disentangling biochemical effects in nanoparticle-based radiotherapy approaches. Abstract : The outcome of radiotherapy can be further improved by combining radiotherapy with nanoparticles. Previous biological studies showed a significant amplification of the biological damage in cells charged with nanoparticles prior to radiotherapy treatments. The rationale has been based on the physical dose enhancement. However, this subject is still a matter of controversy and there are clear indications that biochemical effects may play a key role in the radiosensitization effects of nanoparticles. Within this context, the main goal of our study was to provide new insights into the radiosensitization effects of F98 glioma cells exposed to gadolinium nanoparticles combined with clinical megavoltage beams, and compare them with respect to kilovoltage radiotherapy (commonly used in combination with nanoparticles). For this purpose, we used synchrotron-based Fourier transform infrared microspectroscopy (SR-FTIRM) to provide relevant information on the treatment-induced biochemical changes of the main cell biomolecules. Biochemical differences were evaluated after the treatments to assess cellular damage. Multivariate analysis revealed nanoparticle-dependent changes in megavoltage treated cells. The main spectral variations were related to conformational changes in the protein secondary structures, which might be induced by radiation damage and by changes or rearrangements in the nucleic acid structures due to the initiation of DNA repair mechanisms. We also observed significant changes in the phosphate I and II bands, which concerns DNA damage, while few changes were detected in the lipid region. Spectroscopic data showed that these changes increased as a function of the dose. Finally, PCA analysis did not discriminate clearly between megavoltage and kilovoltage groups treated with nanoparticles, indicating that megavoltage radiosensitization effects might not differ significantly from those in kilovoltage radiotherapy.